2020
DOI: 10.1016/j.tranon.2020.100864
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and clinical value of TIPS combined with subsequent antitumor treatment in HCC patients with refractory ascites

Abstract: Background Currently, hepatocellular carcinoma (HCC) patients with refractory ascites (RA) have a very poor prognosis, and there are no effective treatments recommended by the guidelines. A treatment strategy that utilizes a transjugular intrahepatic portosystemic shunt (TIPS) combined with subsequent antitumor treatment is explored in this study for its feasibility and clinical value. Methods One month after TIPS, the ascites grade and Child-Pugh scores and stages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…All 11 studies (Table 1 ) were retrospective of low to medium quality (Supplementary Table 1 ) and in total included 937 patients, 870 of which with TIPS placement after the diagnosis of HCC to treat the complications. 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Most studies originated from China and the majority had hepatitis B virus‐associated cirrhosis and/or alcohol‐related disease. Patients were mostly male (range: 57.9%–100%) and the mean age ranged from 46.3 to 63.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…All 11 studies (Table 1 ) were retrospective of low to medium quality (Supplementary Table 1 ) and in total included 937 patients, 870 of which with TIPS placement after the diagnosis of HCC to treat the complications. 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Most studies originated from China and the majority had hepatitis B virus‐associated cirrhosis and/or alcohol‐related disease. Patients were mostly male (range: 57.9%–100%) and the mean age ranged from 46.3 to 63.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…In a multicentric study, Huzheng Yan et al [ 27 ] enrolled 68 patients with HCC and portal-hypertension-related refractory ascites. After TIPS implantation, patients were reassessed with the Child–Pugh score and evaluated for anti-HCC treatment.…”
Section: Tips and Locoregional Treatments: Transarterial Chemoemboliz...mentioning
confidence: 99%
“…Recently, a Chinese group of researchers proposed a new flowchart for the downstaging of refractory ascites through the use of antitumor therapy. This flowchart is based on the new BCLC staging: 47.1% of this small cohort of enrolled patients received systemic therapy (namely, sorafenib, lenvatinib, or apatinib) and showed the feasibility and effectiveness of this new sequential treatment of HCC [ 27 ]. Interestingly, the modified step-by-step approach may shorten the distance between BCLC-C and BCLC-D due to CSPH and may extend survival time of patients (from 3 months to 2 years) [ 11 ].…”
Section: Tips Use As a Bridge To Systemic Therapymentioning
confidence: 99%
“…Improvements in CTP scores increase the chances of receiving treatments for HCC, which lead to a survival benefit. 55 TACE, the major treatment modality for HCC, can cause hepatic ischemia through arterial embolization; thus, liver perfusion can be further reduced following TACE in patients with TIPS, which diverts the portal venous inflow. A previous study showed that TACE with drug-eluting beads in HCC patients with TIPS significantly reduced the incidence of hepatotoxicity after TACE and improved the overall survival rate relative to that of conventional TACE.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…In a small number of HCC patients with refractory ascites, TIPS implementation improved CTP scores in 78% of the study population, mainly by controlling ascites. Improvements in CTP scores increase the chance of receiving treatments for HCC, which leads to a survival benefit [ 54 ]. TACE, a major treatment modality for HCC, can cause hepatic ischemia through arterial embolization; therefore, liver perfusion can be further reduced after TACE in patients with TIPS, which diverts the portal venous inflow.…”
Section: Indicationsmentioning
confidence: 99%